2022
DOI: 10.1021/acs.jpclett.2c01945
|View full text |Cite
|
Sign up to set email alerts
|

The Ferroelectric–Ferroelastic Debate about Metal Halide Perovskites

Abstract: Metal halide perovskites (MHPs) are solution-processed materials with exceptional photoconversion efficiencies that have brought a paradigm shift in photovoltaics. The nature of the peculiar optoelectronic properties underlying such astounding performance is still controversial. The existence of ferroelectricity in MHPs and its alleged impact on photovoltaic activity have fueled an intense debate, in which unanimous consensus is still far from being reached. Here we critically review recent experimental and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 79 publications
2
27
0
Order By: Relevance
“…Ambrosio et al have reported that there should be a ferroelastic but not ferroelectric property in organic−inorganic hybrid perovskite, and ferroelectric polarization cannot be sustained when the A-site cation dynamics is fully unleashed. 10 In optoelectronic applications, t h e b r o a d b a n d g a p s o f [ C H 3 P H 3 ] P b I 3 , 1 1 (C 4 H 9 NH 3 ) 2 (NH 3 CH 3 ) 2 Sn 3 Br 10 , 12 and other molecular ferroelectrics are challenging issues as well. On the other hand, CsPbBr 3 quantum dots present ferroelectricity as an example of all-inorganic perovskite halides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambrosio et al have reported that there should be a ferroelastic but not ferroelectric property in organic−inorganic hybrid perovskite, and ferroelectric polarization cannot be sustained when the A-site cation dynamics is fully unleashed. 10 In optoelectronic applications, t h e b r o a d b a n d g a p s o f [ C H 3 P H 3 ] P b I 3 , 1 1 (C 4 H 9 NH 3 ) 2 (NH 3 CH 3 ) 2 Sn 3 Br 10 , 12 and other molecular ferroelectrics are challenging issues as well. On the other hand, CsPbBr 3 quantum dots present ferroelectricity as an example of all-inorganic perovskite halides.…”
Section: Introductionmentioning
confidence: 99%
“…Through the bulk photovoltaic effect, this advantage might help surpass the Shockley–Queisser limit in conventional photovoltaic devices. However, because traditional ferroelectric oxide materials often have a significantly large band gap, they are unable to absorb visible light effectively. Ambrosio et al have reported that there should be a ferroelastic but not ferroelectric property in organic–inorganic hybrid perovskite, and ferroelectric polarization cannot be sustained when the A-site cation dynamics is fully unleashed . In optoelectronic applications, the broad band gaps of [CH 3 PH 3 ]­PbI 3 , (C 4 H 9 NH 3 ) 2 (NH 3 CH 3 ) 2 Sn 3 Br 10 , and other molecular ferroelectrics are challenging issues as well.…”
Section: Introductionmentioning
confidence: 99%
“…63−66 However, the existence of ferroelectricity in hybrid organic−inorganic perovskites is currently a subject of strong debate. 60,67 Additionally, a standard P−E loop has not yet been achieved in MAPbI 3 to the best of our knowledge. Several studies suggest that the orientation of the organic molecules leads to ferroelectric domains, where the tetragonal phase presents a ferroelectric-like behavior.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…An alternative interpretation for the P−E loops is based on the concept of ferroelasticity, which results in a distortion of the crystal lattice, inducing a spontaneous strain in the material. 67 In fact, ferroelastic fingerprints was found to be formed due to the introduction of external strain (caused by epitaxial growth, for example) or the strain caused during the cubic-to-tetragonal phase transition. 71,72 Also, ferroelastic domain formation has a positive influence on charge carrier transport.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation